Implementasi Program Pesta Raya dalam Penguatan Dimensi Kemandirian di SDN 66 Kota Bengkulu - Rizki, Aptania; Sintah, Dewi; Putri, Sella Ayu Eka; Asvio, Nova; Febriani, Hanura (PPSDP Undergraduate Journal of Educational Sciences, 2024)
Strengthening the dimension of independence is not supported by extracurricular activities or extra hours, they look for and memorize dance movements during free class hours at school and home. The Merdeka Curriculum in improving the character of independence held a Raya Festival program to strengthen the Pancasila Student Profile dimension of Independence. This research aims to grow and discover children’s character in the P5 independent curriculum at SDN 66 Bengkulu City. This type of research is qualitative research. This research method uses descriptive qualitative methods. This research showed that 1) the Raya Festival program went well and the activities included dancing, a food bazaar, and an introduction to Bengkulu’s typical culture. This program has fulfilled the aspects of the Pancasila student profile, the dimension of independence. 2) obstacles to implementing the Raya Festival program include time constraints and differences of opinion.